If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(1t + 5) + (4t + 2) = 8 Reorder the terms: -3(5 + 1t) + (4t + 2) = 8 (5 * -3 + 1t * -3) + (4t + 2) = 8 (-15 + -3t) + (4t + 2) = 8 Reorder the terms: -15 + -3t + (2 + 4t) = 8 Remove parenthesis around (2 + 4t) -15 + -3t + 2 + 4t = 8 Reorder the terms: -15 + 2 + -3t + 4t = 8 Combine like terms: -15 + 2 = -13 -13 + -3t + 4t = 8 Combine like terms: -3t + 4t = 1t -13 + 1t = 8 Solving -13 + 1t = 8 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 1t = 8 + 13 Combine like terms: -13 + 13 = 0 0 + 1t = 8 + 13 1t = 8 + 13 Combine like terms: 8 + 13 = 21 1t = 21 Divide each side by '1'. t = 21 Simplifying t = 21
| x=-2(80)+300 | | 4(10x-7)=292 | | 7p-4=1-3p | | 3/5x+8=-12 | | 11m-8=12 | | 3y=800-4(-2y+300) | | 6-4(2x-1)= | | 3x/8=x/2-1 | | 3(2m-4)=18 | | -9b-3=-3[b+2] | | 2(2t-3)=5(2t+3) | | 81=45+5r | | y=4-4(2)+1 | | 21=2x^2+2 | | 2x^2-12y-80=0 | | 5x+(-5x-7)=-3 | | 20+(3*5)=7n | | y=9-12+1 | | 3x-7+2x=23 | | 11n-1=10 | | 12x+1=22 | | y=16-4(4)+1 | | 3x^2+x=6 | | 21(x+8)-12(9+2x)=10(2x+4) | | 1/2+5/x | | (14-8)*9=9m | | 5a^2-3a-2=0 | | x=15+1.5y | | z/4=z/8+4/2 | | (x-1)(x+4)(x-5)=0 | | 5-3(4x-3)=4(2-3x) | | 4=64(0.5)x |